Financial Sector Assessment : Slovenia - World Bank (Washington, DC, 2013)
A joint International Monetary Fund (IMF)-World Bank mission visited Ljubljana, Slovenia during November 6-20, 2000 as part of the IMF-World Bank Financial Sector Assessment Program (FSAP). The principal objective of the mission was to assist the authorities in identifying potential vulnerabilities in the Slovene financial system that could have macroeconomic consequences and to identify directions for reform to reduce these risks. This report provides a summary of the main findings of the mission, and the policy priorities identified.